Analisis Kelayakan Pengoperasian Instalasi Pengolahan Air Limbah (IPAL) CV Proma Tun Probolinggo - Tri Prihatiningsih; Haryono; Imam Marzuki (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
Tofu is a traditional Indonesian food that is very popular with the community. The tofu production process produces solid and liquid waste. The liquid waste contains very high BOD, COD and TSS which has the potential to pollute the environment, therefore it is necessary to have a Waste Water Treatment Plant (WWTP). This study aims to determine the economic feasibility study of the operation of the WWTP. The research was conducted at CV. Proma Tun Saroyyan Probolinggo. To find out the economic feasibility of the operation of WWTPs using the parameters of the Net Present Value (NPV), Payback Period (PP) and Benefit Cost Ratio (B / C R) The results showed that the WWTP used was the Anaerob-Biogas system, the anaerobic system is wastewater treatment by utilizing microorganisms that work without oxygen free, with three stages, namely: Hydrolysis, Acidification, and Methane Formation Stage. The resulting methane gas (biogas) is a mixture of various types of gases, including CH4 (54% -70%), CO2 (27% -45%), O2 (1% -4%), N2 (0.5% -3%), CO (1%), and H2 which are stored in the gas holder and distributed to the community as an alternative fuel to replace LPG gas. For an analysis of economic feasibility with NPV criteria shows that the biogas WWTP is profitable, because the NPV value is positive at Rp. 58,249,000. Based on the criteria of PP, which is 5 years 10 months 20 days, which means that the time is quite short and does not exceed the age of the economical gas holder. And the value of B / C Ratio is 1.4109 which means that the WWTP biogas in the CV. Proma Tun Saroyyan Probolinggo deserves to be developed because of the value of B / C R> 1.